2019
DOI: 10.3390/cells8080873
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Dots in the Neuroglobin-Protein Interaction Network of an Unstressed and Ferroptotic Cell Death Neuroblastoma Model

Abstract: Neuroglobin is a heme protein of which increased levels provide neuroprotection against amyloid proteinopathy and hemorrhagic damage. These cellular stressors involve the promotion of ferroptosis—an iron-dependent, lipid peroxide-accreting form of cell death. Hence, we questioned whether neuroglobin could oppose ferroptosis initiation. We detected human neuroglobin (hNgb)-EGFP-expressing SH-SY5Y cells to be significantly more resistant to ferroptosis induction, identifying 0.68-fold less cell death. To elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 72 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…G6PD is associated with mitochondrial dysfunction 26 and human neuroglobin. It binds proteins of the cellular iron metabolism under ferroptosis stress 27 . Prominin2 ( PROM2 ) can suppress ferroptosis sensitivity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…G6PD is associated with mitochondrial dysfunction 26 and human neuroglobin. It binds proteins of the cellular iron metabolism under ferroptosis stress 27 . Prominin2 ( PROM2 ) can suppress ferroptosis sensitivity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The acute myeloid leukemia cell line NB4 was purchased from the Deutsche Sammlung von Mikroorganismen und Zellkulturen (Braunschweig, Germany). The SH-SY5Y and SH-SY5Y-eGFP [61] neuroblastoma cell lines were kindly provided to us by the laboratory of Prof. Dewilde (University of Antwerp, Belgium) and the multiple myeloma cell line U266 was a gift from Prof. Germeraad (Maastricht University, The Netherlands). Peripheral blood mononuclear cells were isolated from buffy coats of healthy donors, provided by the Red Cross donor center (Red Cross-Flanders, Mechelen, Belgium).…”
Section: Methodsmentioning
confidence: 99%
“…Gilpin et al [ 293 ] found that interaction with Ubiquilin 2 stabilized A1 to maintain protein abundance, and presume that it would have a similar effect on A3, providing a connection to the other pathological A3 observations above. Tangentially, van Acker et al [ 294 ] recently identified an interaction between A3 and neuroglobin, a neuroprotective protein that prevents ferroptosis in response to proteinopathy. During ferroptotic stress, neuroglobin interacts with A3, but the outcome of this interaction is unknown [ 294 ].…”
Section: Hnrnp A3mentioning
confidence: 99%
“…Tangentially, van Acker et al [ 294 ] recently identified an interaction between A3 and neuroglobin, a neuroprotective protein that prevents ferroptosis in response to proteinopathy. During ferroptotic stress, neuroglobin interacts with A3, but the outcome of this interaction is unknown [ 294 ]. Altogether, these findings suggest a greater role for A3 in ALS pathogenesis than just HR and DPR regulation.…”
Section: Hnrnp A3mentioning
confidence: 99%